Development Of Interactive Learning Media For Volleyball Games Based On The Adobe Flash Professional Application Through Student Learning Outcomes - Adlan Nur Rais; Nasuka Nasuka; Agung Wahyudi (STKIP Muhammadiyah Kuningan, 2023)
The objectives of this study are 1) Producing interactive learning media for volleyball games based on the adobe flash professional application to improve student learning outcomes, 2) Knowing and analyzing the level of effectiveness of using interactive learning media adobe flash professional application-based volleyball games to improve student learning outcomes 3) Producing a product that can be helpful to accepted by teachers and students as a means of facilitating the learning process volleyball game. This research uses research and development (R and D) methods with experimental design (before-after). The population in this study was junior high schools at SMPN 1 Tegal, SMPN 5 Tegal, SMPN 6 Tegal, SMPN 7 Tegal, SMPN 8 Tegal, SMPN 14 Tegal, SMPN 15 Tegal, SMPN 17 Tegal, SMPN 18 Tegal and SMPN 19 Tegal. The sampling technique used a saturated sampling of 58 students. The results of this study: 1) Volleyball interactive learning media products based on the adobe flash professional application, which is an application that can be accessed via smartphones and computers. 2) Volleyball interactive learning media products based on the adobe flash professional application are effectively used in learning volleyball forms volleyball theory and practice i. Then the product v itas effect test research showed that volleyball learning media based on adobe flash professional applications have